Probing Xe electronic structure by two-color HHG. (August 2015) - Faccialà, D; Pabst, S; Bruner, B D; Ciriolo, A G; De Silvestri, S; Devetta, M; Dudovich, N; Negro, M; Soifer, H; Stagira, S; Vozzi, C
Synopsis: The aim of this study is probing the multi-electron behavior in xenon by two-color driven high harmonic generation. By changing the relative polarization of the two colors we were able to study different aspects of the multi-electron response.